Inferring the origin and genetic diversity of the introduced wild boar (Sus scrofa) populations in Argentina: an approach from mitochondrial markers - Sagua, Mara Inés (2018)
The Eurasian wild boar (Sus scrofa Linnaeus, 1758) was introduced into Argentina at the beginning of the twentieth century when individuals from Europe were taken to La Pampa province for hunting purposes. Starting from there, a dispersal process began due to the invasive characteristics of the species and to human-mediated translocations. The main objective of this study was to characterize for the first time, the phylogenetic relationships among wild boars from Argentina with those from Uruguay, Europe, Asia, and the Near East, along with diverse domestic pig breeds in order to corroborate the historical information about the origin of the local populations. To this end, we used mitochondrial Control Region and Cytochrome b sequences from sampled Argentinian wild boars and retrieved from GenBank. The results showed that the majority of the Argentinian wild boar populations descend from European lineages, in particular of the E1 clade, according to the historical records. Remarkably, the population of El Palmar National Park had Asian origin that could be attributed to hybridization with local domestic pigs or to unrecorded translocations. Finally, genetic diversity in Argentinian populations was lower than in Europe and Uruguay meaning that wild boar in Argentina is still under the influence of founder effect and has experienced minor genetic introgression from domestic pigs, representing in this sense a reservoir of the original wild boar genetic variability.